2009
DOI: 10.1186/1471-2334-9-26
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of colistin compared with tobramycin for multi-drug resistant Acinetobacter baumannii infections

Abstract: BackgroundNosocomial infections due to multi-drug resistant Acinetobacter baumannii are often treated with colistin, but there are few data comparing its safety and efficacy with other antimicrobials.MethodsA retrospective cohort study of patients treated with colistin or tobramycin for A. baumannii infections in intensive care units (ICUs) at Groote Schuur hospital. Colistin was used for A. baumannii isolates which were resistant to all other available antimicrobials. In the tobramycin group, 53% of the isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 15 publications
2
53
0
4
Order By: Relevance
“…It has been reported that the nephrotoxicity of colistin was not significantly different compared to tobramycin (39), immepenem (32) or ampicillin/sulbactam (42), while the colistin-based treatment had a significantly higher nephrotoxicity than tigecycline-based treatment (36,41).…”
Section: Nephrotoxicitymentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the nephrotoxicity of colistin was not significantly different compared to tobramycin (39), immepenem (32) or ampicillin/sulbactam (42), while the colistin-based treatment had a significantly higher nephrotoxicity than tigecycline-based treatment (36,41).…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…This prospective study found no difference regarding clinical and micrological outcomes in both of the studies. Also, there was no significant difference in ICU mortality between the colistin and tobramycin treatment in infections due to MDR A. baumannii (39 …”
Section: Monotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…[38] A local study found that the risk of nephrotoxicity of colistin (dosed at the relatively low total daily dose of 6 MU of CMS) was similar to that of tobramycin. [39] Colistin's nephrotoxicity is dose-dependent and mostly mild and reversible. [25,38,40] One study showed that rates of nephrotoxicity were significantly higher in patients receiving daily maintenance doses greater than the equivalent of 12 MU of CMS in a 70 kg patient.…”
Section: Nephrotoxicitymentioning
confidence: 99%